A New Smart Antenna for 5/6G Wireless Systems: Narrow 360° Steerable Beam With No Reflectors - Pirapaharan, K.; Hoole, P.R.P.; Kunsei, H.; Senthilkumar, K.S.; Hoole, S.R.H. (Smart Antennas and Electromagnetic Signal Processing for Advanced Wireless Technology, 2020)
In this chapter is presented a computationally efficient and fast method to construct smart antennas using an analytical, phase shift technique. A phase shifting method for a nonlinear array antenna is described. The array antenna elements are arranged in a regular polygon geometry, and it is shown that by controlling the electronic signal phase of the array elements, without any extra calculations as in most smart antennas, the antenna beam may be steered through 360°. Moreover, it is only a single beam that is generated, with minimal side lobes and no back lobes so that the wireless system is specifically focused toward a single direction, minimizing interference from other transmitters or multipath.